B-cell function in common variable immunodeficiency: suppression of in vitro anti-sheep erythrocytes antibody production by T cells and monocytes. - Pollack, S (1985)
Peripheral blood mononuclear (PBM) cells from five of 21 patients with common variable immunodeficiency (CVI) stimulated in vitro by antigen produced antibodies normally. In 11 of the 16 non-responders, removal of adherent suppressor cells by Sephadex G-10 or removal of monocytes or OKT8 positive suppressor lymphocytes by other means of separation made antibody responses demonstrable. Cells adherent to the G-10 column had suppressor function in the autologous antigen driven system; the suppressor activity appeared to be due to adherent T cells in some patients and to adherent monocytes in others. The suppressor cell functions in these patients did not correlate significantly with the number of cells positive for monoclonal antibodies OKT8 or Leu-2. Factors suppressing antibody production in this system were found in normal serum but usually not in serum of the patients with CVI studied. Substances in normal serum which enhance antibody production in this system when added late in culture were present in serum of patients with CVI. Any abnormality of interleukin-1 production by monocytes of these patients did not seem relevant to the immunodeficiency.